Analisis Strategi Pemasaran Digital dalam Mendorong Pertumbuhan Usaha Kewirausahaan Sosial - Novita, Yulia (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to conduct an analysis of digital marketing strategies in encouraging the growth of social entrepreneurship businesses. The research method uses a quantitative descriptive method with data collection techniques using observation, questionnaires and literature studies, while data analysis uses data quality tests, classical assumption tests, simple linear regression tests, t-tests and determination coefficient tests. The sample in this study amounted to 100 respondents. The results of the study of digital marketing strategy analysis in encouraging the growth of social entrepreneurship businesses in the younger generation, especially from Generation Z and the millennial generation, that digital marketing strategy analysis has a significant positive influence in encouraging the growth of social entrepreneurship businesses in Riau Province. The findings of the study are expected to add valuable insights for researchers, practitioners, and policy makers in developing more effective and efficient strategies in supporting the practice of social entrepreneurship growth and community empowerment.